The contribution of pathways initiated via the Gq\11 G-protein family to atrial fibrillation. (March 2016) - Tinker, Andrew; Finlay, Malcom; Nobles, Muriel; Opel, Aaisha
Graphical abstract: Abstract: Atrial fibrillation is the commonest cardiac arrhythmia and leads to significant clinical morbidity and mortality. It has a complex pathophysiology but is often initiated by atrial ectopic beats and because of atrial remodelling once it occurs it can become established. Thus therapeutic interventions designed to prevent the initial occurrence of the arrhythmia are particularly needed. At the cellular level, these ectopic beats arise because of abnormal calcium release events from the sarcoplasmic reticulum leading to an inward current mediated by the sodium-calcium exchanger. There has been considerable interest in this over the last few years largely focused on the ryanodine receptor and related signalling pathways. However, atrial myocytes also possess a well-developed inositol trisphosphate (IP3 ) dependent calcium release system and this has been less studied. In this review we focus on pathways and molecules that couple via the Gq\11 family of G-proteins including regulators of G-protein signalling that may influence IP3 mediated calcium release and atrial fibrillation.